Resin composite aggregated S-PRG particles are not superior to non-S-PRG under microcosm biofilm - Freire, Andrea; Bento, Victor Augusto Alves [UNESP]; Jussiani, Eduardo Inocente; Andrello, Avacir Casanova; Marques, Maria Carolina Silva (Springer Nature, 2025)
This study assessed the effect of composite resins, aggregated or not with S-PRG particles, and the use of toothpaste in controlling demineralization and bacterial growth. Human molars were distributed into 3 groups: control (CT) – sound teeth, Beautifil Bulk Restorative System (aggregated with S-PRG) (BB), Filtek One Bulk Fill (without S-PRG) (FB). Teeth destined for groups BB and FB previously received Class I preparations (4 × 4 × 4 mm), followed by single-increment restorations. All teeth were sectioned mesiodistally, with all specimens subjected to cariogenic challenge for 5 days, including microcosm biofilm formation. Half of each tooth was exposed to toothpaste (CTF, BBF, FBF). The loss of microhardness was assessed considering the initial microhardness as 100% on enamel, dentin, and composite resin substrates. Colony Forming Units (CFU/mL) were counted in 3 media. Data analysis used one-way ANOVA, Tukey HSD test, and paired t-test (α = 0.05). Toothpaste significantly reduced CFU/mL for total bacteria and genus Streptococcus (p < 0.05), with no significant difference for Streptococcus mutans. Enamel microhardness was positively affected by toothpaste. Both restorative systems controlled enamel demineralization, with FB and FBF outperforming BB and BBF. There was minor degradation of both composite resins, between 10% and 22%. Toothpaste effectively reduced microorganisms, irrespective of the composite resin. Regarding demineralization control, both restorative systems, with and without S-PRG particles, were effective on enamel.
Keywords: Demineralization; Dental caries; Resin composite; Secondary caries; Toothpaste